2000
DOI: 10.1258/0004563001899870
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical investigation of suspected rhabdomyolysis

Abstract: This article was prepared at the invitation of the Clinical Laboratory Investigations Standing Committee of the Association of Clinical Biochemists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 40 publications
3
70
1
1
Order By: Relevance
“…It is commonly seen in trauma and electrical burns patients. To prevent morbidity and mortality from ARF due to rhabdomyolysis, early detection of ARF by monitoring the biochemical parameters such as serum creatinine, serum creatine kinase (CK), and urinary myoglobin (UM) can be helpful [2]. We performed this study in trauma and electrical burns patients to evaluate the use of these biochemical parameters for early prediction of highrisk patients who tend to develop ARF.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly seen in trauma and electrical burns patients. To prevent morbidity and mortality from ARF due to rhabdomyolysis, early detection of ARF by monitoring the biochemical parameters such as serum creatinine, serum creatine kinase (CK), and urinary myoglobin (UM) can be helpful [2]. We performed this study in trauma and electrical burns patients to evaluate the use of these biochemical parameters for early prediction of highrisk patients who tend to develop ARF.…”
Section: Introductionmentioning
confidence: 99%
“…The literature describes, using rat and cell culture models [22][23][24][25][26][27] , the deleterious role of this protein, specifically the heme prosthetic group, in the tubular endothelium. This role is associated with the production of reactive oxygen species (ROS) and free radicals in the mitochondria, which initiate lipid peroxidation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 13 patients with rhabdomyolysis, Lappalainen [108] found that the average times to reach the 50% level of initial values were 12 hours for myoglobin and 42 hours for CK ( P < 0.01). In a review of laboratory investigations, Beetham [109] concluded that serum CK levels should be used to screen patients with suspected rhabdomyolysis and that there is no reason for laboratories to have assays for myoglobin available until further studies are able to demonstrate its utility. …”
Section: Assessing Risk Of Renal Failurementioning
confidence: 99%